2021
DOI: 10.1158/1078-0432.ccr-21-0417
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Blood-Based Multi-cancer Detection in Plasma Cell-Free DNA

Abstract: equity in the company. KNK holds stock in Illumina, Inc. GRO is an employee of Foundation Medicine with equity in Roche. MVS is an employee of, and shareholder in, McKesson Corporation, and is a clinical advisor/serves on the advisory board for GRAIL. EAK is a consultant for GRAIL, Inc. and Cellanyx, LLC. The Mayo Clinic was compensated for MCL's advisory board activities for GRAIL, Inc.Research.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 46 publications
5
54
0
Order By: Relevance
“…However, more clinical trials are required for verifying these findings and for providing the standard operation procedure. Moreover, ctDNA testing has attracted great attention in early tumor detection of several common cancer types (57,(85)(86)(87), although it is still a long way to apply ctDNA testing in the clinical routine.…”
Section: Discussionmentioning
confidence: 99%
“…However, more clinical trials are required for verifying these findings and for providing the standard operation procedure. Moreover, ctDNA testing has attracted great attention in early tumor detection of several common cancer types (57,(85)(86)(87), although it is still a long way to apply ctDNA testing in the clinical routine.…”
Section: Discussionmentioning
confidence: 99%
“…Biological factors associated with tumor DNA shedding include tumor volume and tumor surface area, vascularization, tumor cell growth and death rates, mitotic and metabolic activity, and cell morphology. Furthermore, cancer signal detection is associated with active proliferation and explains why more aggressive cancers tend to shed more DNA into the bloodstream [ 135 ]. In fact, longitudinal follow-up data to evaluate the prognostic significance of a multi-cancer early detection (MCED) test has suggested that this test detected more clinically significant cancers and that detection was prognostic beyond clinical stage and method of clinical diagnosis.…”
Section: Current Status Of Clinical Use Of Ctdna Testing In Patients ...mentioning
confidence: 99%
“…In fact, longitudinal follow-up data to evaluate the prognostic significance of a multi-cancer early detection (MCED) test has suggested that this test detected more clinically significant cancers and that detection was prognostic beyond clinical stage and method of clinical diagnosis. Accordingly, cancers not detected by the MCED test tended to be less aggressive [ 135 ]. Hence, biological differences in shedding rates may explain the differences in sensitivity between various tumors and high ctDNA levels may be an indication for more aggressive cancers.…”
Section: Current Status Of Clinical Use Of Ctdna Testing In Patients ...mentioning
confidence: 99%
“…However, more than 90% of those who were negative for ctDNA did not relapse [ 13 ]. Since then, the prognostic value of ctDNA was repeatedly confirmed [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 18 , 19 ]. Similar to other tumor markers, ctDNA can also be used to monitor disease progression.…”
Section: Clinical Applications Of Ctdnamentioning
confidence: 99%
“…Importantly, it is well-established that the amount of ctDNA is proportional to tumor size (tumor burden) and is related to other clinicopathological parameters such as stage, lymph node infiltration, local and distant metastasis, and disease-free and overall survival [ 8 , 9 ]. Thus, ctDNA carries strong prognostic information [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%